2011 4th International Congress on Image and Signal Processing 2011
DOI: 10.1109/cisp.2011.6100025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of upper-limb positions on motion pattern recognition using electromyography

Abstract: Previous studies of electromyographic (EMG) pattern recognition for neural prosthesis control mainly focused on the estimation of offline classification accuracy. Factors that may affect the performance in operating prosthesis in practice were rarely considered. In the preliminary study we investigated effects of the variation of limb positions on classification performance. Eight channels of myoelectric signals and a LDA classifier were used to identify seven classes of forearm movements in five transradial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 6 publications
2
26
0
Order By: Relevance
“…Scheme et al demonstrated that training the classifier in multiple positions reduces this degradation [14]. Chen et al performed a similar study using data from participants with transradial amputation and supported the notion that training the classifier in multiple positions reduces the position effect [17]. In another study, Scheme et al further showed that changing the limb position during both static and dynamic ADLs negatively affects myoelectric pattern recognition [15].…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Scheme et al demonstrated that training the classifier in multiple positions reduces this degradation [14]. Chen et al performed a similar study using data from participants with transradial amputation and supported the notion that training the classifier in multiple positions reduces the position effect [17]. In another study, Scheme et al further showed that changing the limb position during both static and dynamic ADLs negatively affects myoelectric pattern recognition [15].…”
Section: Introductionmentioning
confidence: 62%
“…The results of applying HD-FMG for classification were compared with those of standard pattern recognition-based EMG control methods reported in the literature [13][14][15][16][17][18]. As shown in Figure 7, the mean overall error was 0.33 percent using pressure maps, while errors between 2.2 and 11.3 percent have been commonly reported using EMG signals [13][14][15][16][17][18].…”
Section: Hand Motion Classificationmentioning
confidence: 99%
See 3 more Smart Citations